Emerging Antifungal Resistance in Fungal Pathogens - Hui,ST; Gifford,H; Rhodes,J (Current Clinical Microbiology Reports, 2024)
Purpose of Review: Over recent decades, the number of outbreaks caused by fungi has increased for humans, plants (including important crop species) and animals. Yet this problem is compounded by emerging antifungal drug resistance in pathogenic species. Resistance develops over time when fungi are exposed to drugs either in the patient or in the environment. Recent Findings: Novel resistant variants of fungal pathogens that were previously susceptible are evolving (such as Aspergillus fumigatus) as well as newly emerging fungal species that are displaying antifungal resistance profiles (e.g. Candida auris and Trichophyton indotineae). Summary: This review highlights the important topic of emerging antifungal resistance in fungal pathogens and how it evolved, as well as how this relates to a growing public health burden.